Economic Benefits of Globalization: Comparative Analysis between Peru and Mexico (2013-2023) - Nizama Reyes, Mario Enrique (2026)
The phenomenon of globalization has had a significant impact on both Peru and Mexico in various areas, such as the economy, technology, and society. Therefore, it is relevant to comparatively analyze the economic benefits in both countries. The research question addressed was: What are the economic benefits of globalization, based on a comparative analysis of Peru and Mexico from 2013 to 2023? The objective was to comparatively analyze the economic benefits of globalization in Peru and Mexico during the period 2013–2023. Among the most notable findings, regarding the evolution of metal exports between 2013 and 2023, copper was the most important metal for Peru, with its export volume (in metric tons) growing from 1,377,000 in 2013 to 2,755,066; for Mexico, copper was also the most important exported metal, reaching its peak value in 2018 at 455,429.20 metric tons. In conclusion, both countries have experienced significant economic growth thanks to globalization, primarily in the mineral export sector. However, economic growth has been more volatile in Peru due to its dependence on mining exports and recent political instability, in contrast to Mexico, which has shown greater stability thanks to its diversified economy.